Perineuronal nets in motor circuitry regulate the performance of learned vocalizations in songbirds - Xinghaoyun Wan; Angela S. Wang; Daria-Salina Storch; Vivian Y. Li; Jon T. Sakata (Communications Biology)
Abstract The accurate and reliable performance of learned vocalizations (e.g., speech and birdsong) modulates the efficacy of communication in humans and songbirds. Consequently, it is critical to understand the factors that regulate the performance of learned vocalizations. Across taxa, neural circuits underlying motor learning and control are replete with perineuronal nets (PNNs), and we analyzed how PNNs in vocal motor circuitry regulate the performance of learned song in zebra finches. We report that developmental increases in PNN expression in vocal circuitry are associated with developmental increases in song stereotypy. We also document that enzymatically degrading PNNs in the motor nucleus HVC acutely altered song structure (changes in syllable sequencing and production). Collectively, our data reveal a causal contribution of PNNs to the performance of learned behaviors and, given the parallels in the regulation of birdsong and speech, suggest that PNNs in motor circuitry could modulate speech performance.